Research progress on pharmacological properties and application of probiotics in the fermentation of Scutellaria baicalensis Georgi - Guo, Fangyu; Li, Chunhai; Dou, Jiaxin; Liang, Jie; Chen, Zouquan; Xu, Zhenshang; Wang, Ting (Frontiers in Nutrition, 2024)
Scutellaria baicalensis Georgi, is a medicinal herb with a rich history of use in traditional Chinese medicine. This review concentrates on the chemical constituents of Scutellaria baicalensis Georgi, with a particular emphasis on flavonoids such as baicalin, baicalein, and wogonin. Additionally, it examines the effects of probiotic fermentation on the plant's chemical profile and pharmacological actions. Evidence suggests that probiotic fermentation markedly modifies the bioactive components of Scutellaria baicalensis Georgi, thereby augmenting its medicinal potency. The paper delves into the mechanisms by which the primary active constituents of Scutellaria baicalensis Georgi are altered during fermentation and how these changes influence its pharmacological properties. This review aims to lay a theoretical groundwork for the clinical utilization of Scutellaria baicalensis Georgi and the formulation of innovative therapeutic approaches.